Sheehan syndrome - Özkan, Y; Colak, R (Maghira & Maas Publications, 2005)
Sheehan syndrome (SS) or post-partum pituitary necrosis is a pituitary insufficiency secondary to excessive post-partum blood losses. SS is a very significant cause of maternal morbidity and mortality in developing countries although it is a rarity in developed countries in which obstetrical care has been improved. In this study, we reviewed 20 cases retrospectively who were diagnosed as SS in our clinic. The patients aged 40 to 65 years with a mean age of 51.12 +/- 9.44 years (mean +/- SD). Time to make a definitive diagnosis of the disease ranged between 5 and 25 years with a mean of 16.35 +/- 4.74 years. Three of our patient (15%) had a previous diagnosis of SS. Three patients (15%) were referred to emergency service for hypoglycemia, three patients (15%) for hypothyroidism and one patient (5%) for hyponatremia. Dynamic examination of the pituitary revealed GH, Prolactin, FSH, TSH and ACTH insufficiency in all of the patients. One of our patients had a sufficient LH response to LHRH challenge. All of the patients were imaged with pituitary MRI. Eleven patients had empty sella and 9 patients had partial empty sella. SS is still a common problem in our country, especially in rural areas. Considering the duration of disease, important delays occur in diagnosis and treatment of the disease.
Keywords: Sheehan syndrome; pituitary insufficiency; empty sella